Legal Framework Boosting Green Economy: Evidence from the Power Development Plan VIII - Thang, Le Ngoc (VNU Journal of Science: Legal Studies, 2025)
Currently, climate change, environmental pollution, and the depletion of natural resources are becoming major challenges in the world as well as in Vietnam. In this context, the green economy has emerged as a key driver of sustainable development, promoting clean technologies and optimizing the use of natural resources. The Power Development Plan VIII, approved in May 2023, plays an important role in Vietnam's energy development strategy. The Plan is considered one of the key strategies for implementing sustainable development goals and dealing with climate change. This paper provides an overview of the green economy and the VIII Electricity Planning, analyzes the current legal regulations and their role in promoting the green economy. The paper also provides recommendations derived from this analysis, enhancing the effective implementation of the Power Development Plan VIII, establishing a flexible and effective legal framework in boosting the green economy, and achieving the sustainable development goals of Vietnam.